The learning outcomes in the study program format of school subjects belonging to the General Training Area at UJAT: A syntactic and semantic analysis - Pérez Hernández, Abel Federico; Pérez Arellano, Pedro; Méndez Sánchez, Cristian Janet (Perspectivas Docentes, 2016)
This paper presents the results of the analysis performed on the data field called learning outcomes, which is part of the format better known as Study Program, used for subjects in all of the professional careers of the Universidad Juárez Autónoma de Tabasco, in order to identify opportunities for improvement in the syntactic and semantic wording of this data field. The observed results of the nine programs reviewed, belonging to the General Training Area, lead to the conclusion that a weak culture in structuring and formulation of learning outcomes, bythose who developed, reviewed and evaluated the Study Programs, is shown. The various stakeholders involved in this process will find it difficult to carry out this task if they have not received training to enable them to write down and evaluate learning outcomes properly. This process of analysis is applicable to any study program format including in its development a data field called learning outcomes, in an educational context.
Keywords: Study program; learning outcomes; syntactic wording; semantic wording